Defect localization in high-power vertical cavity surface emitting laser arrays by means of reverse biased emission microscopy. (9th June 2021) - Fabbro, Robert; Haber, Thomas; Fasching, Gernot; Coppeta, Raffaele; Pusterhofer, Michael; Grogger, Werner
Abstract: Applying a reverse bias near the breakdown voltage results in photon emission at the pn-junction in vertical cavity surface emitting lasers (VCSELs). This radiation can be collected with an emission microscope. Here, this technique is employed to investigate a high-power two dimensional (2D) VCSEL array with a large number of emitters at a non-degraded state and after high electrical stress. It has been found that non-degraded arrays show varying photon intensities across all emitters at breakdown condition while degraded arrays exhibit more intense electroluminescence at areas with faulty emitters containing defects in the active area as confirmed by plan view scanning transmission electron microscopy analysis.